New Migration Stream between Mexico and Canada - Douglas S. Massey; Amelia E. Brown (El Colegio de la Frontera Norte, A.C., 2011)
Data from the Mexican Migration Project is used to contrast processes of Mexican migration to Canada and the United States. All migrants to Canada entered through the Seasonal Agricultural Worker Program and migration there is strongly predicted by marital status and number of dependents. Conversely, most migrants to the United States are undocumented and thus self-selected without regard to marital status or parenthood. Migrants to Canada enjoy superior labor market outcomes with higher wages and more compact work schedules that yield higher earnings and shorter periods away from families. Labor migration to Canada also tends to operate as a circular flow with considerable repeat migration whereas undocumented migrants to the United States tend to stay longer, since crossing the Mexico-U.S. border has become increasingly difficult.